Enkapsulasi bakteri asam laktat dari tempoyak asal Jambi: Pengaruh konsentrasi alginat [Encapsulation of lactic acid bacteria isolated from fermented durian (tempoyak) in Jambi: Influence of alginate concentration] - Addion Nizori; Nanda Prayogi; Ika Gusriani; Lavlinesia Lavlinesia; Arzita Arzita (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
This study aimed to investigate the characteristics and the viability of encapsulated lactic acid bacteria (LAB) from fermented durian from Jambi using alginate concentration as wall material. The encapsulation method used the emulsification technique where LAB in alginate capsules was formed by the formation of water in oil emulsion. This study used a completely randomized design with various alginate concentrations as the treatments with concentrations: 1%, 3%, 5%, 7%, and 9%, respectively. The result showed that alginate concentration on LAB microcapsules was very significant in yield, pH, and heat resistance. All treatment concentrations provided high LAB viability, so alginate is effective for wall material LAB encapsulation with emulsification techniques.  The best LAB microcapsule was 7% of alginate concentration with value of yield 5,60 %, viability of LAB log 12,43 CFU/g, pH 5,22, heat resistant on 50ºC (log 12, 46 CFU/g), 60ºC (log 12,45 CFU/g), 70ºC (log 12,35 CFU/g).